2019
DOI: 10.1530/rep-18-0523
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in reproductive medicine

Abstract: Artificial intelligence (AI) has experienced rapid growth over the past few years, moving from the experimental to the implementation phase in various fields, including medicine. Advances in learning algorithms and theories, the availability of large datasets and improvements in computing power have contributed to breakthroughs in current AI applications. Machine learning (ML), a subset of AI, allows computers to detect patterns from large complex datasets automatically and uses these patterns to make predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 128 publications
0
78
0
8
Order By: Relevance
“…Convolutional neural network (CNN), a kind of an artificial neural network, has shown excellent promise in reading fundus and skin photographs 16 , 17 . Machine learning has therefore been rapidly incorportaed in radiology, cardiology, gastroenterology, and even reproductive medicine 18 21 . Machine learning has already been introduced in colposcopic imaging; however, available evidence on its specificity and sensitivity is limited, preventing its full use in this field 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural network (CNN), a kind of an artificial neural network, has shown excellent promise in reading fundus and skin photographs 16 , 17 . Machine learning has therefore been rapidly incorportaed in radiology, cardiology, gastroenterology, and even reproductive medicine 18 21 . Machine learning has already been introduced in colposcopic imaging; however, available evidence on its specificity and sensitivity is limited, preventing its full use in this field 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Embryologists may choose to exclusively perform ICSI in these cycles in order to keep high fertilization rates [ 141 ]. Moreover, in this new era of artificial intelligence in IVF laboratories, time-lapse technology, when possible, may provide important information on the development of these embryos [ 142 , 143 ]. Further to that, as poor responders mainly refer to women of advanced maternal age and previous failed attempts, we may consider employing preimplantation genetic testing for aneuploidy to ensure the chromosomal integrity of the embryos prior to embryo transfer [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study utilized a DL model for automated embryo quality evaluation by analyzing timelapse images [85]. The impact of AI in IVF and embryo selection are viewed in different papers [3,86,14,25].…”
Section: Opportunity Analysis For Ml-based Embryo Selectionmentioning
confidence: 99%
“…It is confirmed that ML algorithms have an advantage over logistic regression for the prediction of the IVF outcome in assisting fertility specialists to counsel their patients and adjusting the appropriate treatment strategy [13]. The fundamental aspects of AI and ML in reproductive medicine were addressed in terms of applications, limitations, and challenges in the review [14].…”
Section: Introductionmentioning
confidence: 99%